Materiais did?ticos manipul?veis para o ensino e aprendizagem da Astronomia para estudantes com defici?ncia intelectual - Capistrano, Liz Leal Mota (2024)
The present work refers to intervention research that aims to produce manipulable teaching materials for teaching and learning Astronomy for students with Intellectual Disabilities (ID). The idea was to enable students with ID to reflect on the topic of Astronomy, focusing on the study of the Solar System, proposing an alternative method, based on the construction of knowledge through the production of manipulable teaching materials, allowing them a new learning experience. The research methodology adopted was qualitative in nature, whose modality is research with direct intervention in the reality of the subjects involved. The target audience for the work were students with ID from the Pedagogical Assistance Center for People with Special Educational Needs (CAPENE) located in the city of Serrinha, making a total of 5 students. We chose CAPENE to develop the research, as it is an institution structured to offer AEE Specialized Educational Services and a multidisciplinary team. To confirm some of the hypotheses raised, it was necessary to carry out the same workshop in a regular room with a student with ID enrolled. Therefore, at Col?gio Municipal Centro Social Urbano, a regular room with students with ID was chosen to develop the Teaching Materials Kit. Carrying out the workshop made it possible to glimpse the learning of students with ID. The research consisted of fieldwork that involved a diagnostic assessment of prior knowledge, observations, construction of teaching material, as well as the carrying out of practical activities that allowed establishing relationships and building knowledge in Astronomy. The educational product linked to this work consists of a Teaching Materials Kit, composed of a Solar Twister Game, a Model of the Solar System, a Star Cluster Puzzle and a Memory Game with elements of the Solar System. The research result contributed to Meaningful Learning in the introduction of concepts related to Astronomy, enabling students to build knowledge that could serve as anchors for future concepts. In this way, we hope to contribute to the development of inclusive proposals for people with intellectual disabilities in the field of Astronomy in the municipality of Serrinha, where there are few activities aimed at this specific purpose.